Cameroon's crustal configuration from global gravity and topographic models and seismic data. (January 2020) - Kemgang Ghomsi, Franck Eitel; Sévérin, Nguiya; Mandal, Animesh; Nyam, Françoise Enyegue A.; Tenzer, Robert; Tokam Kamga, Alain P.; Nouayou, Robert
Abstract: We use gravity information obtained from the XGM2016 global gravitational model together with topographic, bathymetric and seismic data to interpret the crustal structure beneath Cameroon and adjoined geological regions. For this purpose, we apply the regularized non-linear gravity inversion for a gravimetric determination of the Moho depth utilizing existing results of seismic data analysis as constraints. The estimated Moho model reflects regional tectonic configuration and geological structure of this region, mainly consisting of two major geological units, i.e. the Cameroon Volcanic Line and the Congo Craton. A validation of gravimetric result at sites of the Cameroon Broadband Seismic Experiment (CBSE) reveals overall similarities between gravimetric and seismic estimates. A comparison of our result is also conducted with previously published results. The cross-comparison of these results reveals a good agreement between them, particularly beneath the Cameroon Volcanic Line, the Adamawa Plateau and the Garoua Rift. Nevertheless, some relatively large inconsistencies roughly reaching ±10 km in estimated values of the Moho depth are identified in geological regions of the Congo Craton and the Yaoundé domain. The spatial correlation analysis between the Moho geometry and the topography indicates an isostatic state of particular geological units, suggesting their compensation stage. Our result closely agrees with the assumption that most of isostatically over compensated geological structures were formed during a compressional tectonic regime, except for the Garoua Rift that was likely formed during an extensional regime. We also computed the Bouguer gravity data at different constant elevations above sea level in order to supress a gravitational signature of shallower sources, while enhancing a gravitational signature from deeper crustal and lithospheric structures, focusing primarily on cores of major cratonic formations. The Bouguer gravity maps indicate that the Yaoundé domain likely represents the crustal manifestation of the suture zone between the Congo Craton and the Adamawa-Yadé domain, acting as a micro-continent. Highlights: Highlights (85 characters maximum by bullet, space included): We produced a new high-resolution gravity derived Moho model for Cameroon. We found thicker Moho depth beneath the Ntem complex and the Adamawa Plateau. The Moho under the Mount Cameroon deepens to only about 30 km. Our crustal thickness model revealed E-W trending along with the Oubanguides Belt.